The Structure of Hiring Costs in Germany: Evidence from Firm-Level Data - Samuel Mühlemann; Harald Pfeifer (Institute for the Study of Labor (IZA), 2013)
This paper analyzes the structure of hiring costs of skilled workers in Germany. Using detailed and representative firm-level data on recruitment and adaptation costs of new hires, we find that average hiring costs amount to more than 8 weeks of wage payments (4,700 Euros). The structure of hiring costs is convex, as an increase in the number of hires by 1% increases hiring costs by 1.3%. We find moderate effects of labor market institutions on the magnitude but none on the structure of hiring costs. Furthermore, we provide evidence in favor of monopsony power in the German labor market.
Keywords: J32; J63; 330; labor adjustment costs; hiring costs; search costs; adaptation costs